Revisiting the vortex-core tunnelling spectroscopy in YBa2Cu3O7−δ - Jens Bruér (Nature Portfolio, 2016)
Quantized subgap states measured in the vortex cores of YBa2Cu3O7−δhave been challenging theory for over twenty years. Here, the authors show that these spectral features identified as vortex-core states exist independent of vortices, which calls for revisiting vortices in cuprate superconductors.